Studi Retrospektif Penggunaan Antibiotik pada Pasien Covid-19 dengan Pneumonia di Rumah Sakit “X” Provinsi Bali, Indonesia - Siada, Nyoman Budiartha; Juanita, Rr Asih; Sanjaya, Dwi Arymbhi; Meriyani, Herleeyana (Jurnal Ilmiah Medicamento, 2024)
COVID-19 with bacterial pneumonia co-infection is a condition with bacteria present in COVID-19 patients. The prevalence of bacterial co-infection in COVID-19 patients ranges from 12.4%–50%. This study aims to determine the relationship between the appropriate use of antibiotics and the severity of inpatients with COVID-19 and pneumonia co-infection at Hospital "X" Bali Province, Indonesia. This research is an observational study with a cross-sectional approach. Data collection was carried out retrospectively on medical record data of COVID-19 inpatients with pneumonia co-infection at Hospital "X" Bali Province, Indonesia for the period January - December 2021. The sampling technique used total sampling according to inclusion and exclusion criteria. Appropriate use of antibiotics antibiotic was analyzed using Pharmaceutical Care Network Europe (PCNE) version 9.1. The patient severity index was an assessment based on the Pneumonia Severity Index (PSI) score. The relationship between the appropriate use of antibiotics and the severity of inpatients with COVID-19 and pneumonia co-infection was analyzed using Fisher's test. Of the 80 COVID-19 inpatients with pneumonia co-infection, 90% experienced inappropriate use of antibiotics. Fisher's test results showed that there was no significant relationship between the appropriate use of antibiotics and the severity of inpatients with COVID-19 and pneumonia co-infection at Hospital "X" Bali Province, Indonesia (p > 0.05).